Sequence and Phylogenetic Analysis of Human T Cell Lymphotropic Virus Type 1 from Tumaco, Colombia (2003)
ABSTRACT: Human T cell lymphotropic virus type 1 (HTLV-1) is a retrovirus that causes leukemia and the neurological disorder HTLV-1 associated myelopathy or tropical spastic paraparesis (HAM/TSP). Infection with this virus - although it is distributed worldwide - is limited to certain endemic areas of the world. Despite its specific distribution and slow mutation rate, molecular epidemiology on this virus has been useful to follow the movements of human populations and routes of virus spread to different continents. In the present study, we analyzed the genetic variability of a region of the env gene of isolates obtained from individuals of African origin that live on the Pacific coast of Colombia. Sequencing and comparison of the fragment with the same fragment from different HTLV-1 isolates showed a variability ranging from 0.8% to 1.2%. Phylogenetic studies permit us to include these isolates in the transcontinental subgroup A in which samples isolated from Brazil and Chile are also found. Further analyses will be necessary to determine if these isolates were recently introduced into the American continent or if they rather correspond to isolates introduced during the Paleolithic period.